Herding and overconfidence to investment decisions: Evidence from stock and cryptocurrency investors in Indonesia - Mega Noerman Ningtyas; Avicenna Raihan Kusuma; Muhammad Riza Hafizi (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2026)
This study examines how herding behavior and overconfidence influence investment decisions among stock and cryptocurrency investors. The rapid growth of retail participation in both markets raises concerns about the role of behavioral biases in shaping investors’ decision-making processes. Prior studies have explored these biases within individual markets, but there is limited empirical evidence directly comparing their effects across stock and cryptocurrency investors. Using a quantitative approach, data were collected from 442 investors in Indonesia through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) and Multi-Group Analysis to compare stock and cryptocurrency investors. The results show that both herding behavior and overconfidence positively influence investment decisions. Multi-group analysis reveals that the effect of herding behavior differs significantly between stock and cryptocurrency investors, while the effect of overconfidence does not differ between the two markets. These findings highlight the important role of behavioral biases in investment decision-making and suggest that improving investors’ awareness of psychological biases may help promote more rational investment behavior in financial markets.